EFFECT OF AUTOMOTIVE PERFORMANCE LEARNING WORK PRACTICES AND PERFORMANCE INDUSTRY OF interest in entrepreneurship LIGHT VEHICLE ENGINEERING XII SMK PIRI 1 YOGYAKARTA 2013/2014 - Rachmat Udin; Supriyoko Supriyoko (Universitas Sarjanawiyata Tamansiswa, 2014)
The hypothesis of this study were (1) there is a positive influence on learning achievement automotive interest in entrepreneurship, (2) there is a positive influence on the industry work practices accomplishment interest in entrepreneurship, (3) there is a positive effect of learning achievement and achievement automotive industry work practices together to class XII student interest in entrepreneurship minor engineering vehicles SMK Piri 1 Yogyakarta Academic Year 2013/2014.Â This research is a kind of ex - post facto research . The population in this study is a class XII student of SMK Piri 1Yogyakarta TKR which is 129 students, with a sample of 98 students. Data capture techniques using methods of documentation, test and questionnaire. The validity of the questionnaire instrument carried by grain analysis using Product Moment Correlation formula and reliability testing using Cronbach Alpha. Anlisis Analysis using partial correlation and multiple regression, which previously conducted test requirements analysis includes tests of normality, linearity and intercorrelations.Â The results showed that (1) learning achievement and achievement automotive industry work practices together positive and significant effect on the interest in entrepreneurship. (2) The learning achievement of automotive positive and significant effect on the interest in entrepreneurship. (3) Achievement industry work practices and a significant positive effect on the interest in entrepreneurship. This shows that learning achievement automotive (X1) and the achievement of industrial work practices (X2) has the effect of interest in entrepreneurship (Y).